(6)x*x-14x=12

Simple and best practice solution for (6)x*x-14x=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6)x*x-14x=12 equation:


Simplifying
(6) * x * x + -14x = 12

Multiply x * x
6x2 + -14x = 12

Reorder the terms:
-14x + 6x2 = 12

Solving
-14x + 6x2 = 12

Solving for variable 'x'.

Reorder the terms:
-12 + -14x + 6x2 = 12 + -12

Combine like terms: 12 + -12 = 0
-12 + -14x + 6x2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-6 + -7x + 3x2) = 0

Factor a trinomial.
2((-2 + -3x)(3 + -1x)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-2 + -3x)' equal to zero and attempt to solve: Simplifying -2 + -3x = 0 Solving -2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -3x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -3x = 0 + 2 -3x = 0 + 2 Combine like terms: 0 + 2 = 2 -3x = 2 Divide each side by '-3'. x = -0.6666666667 Simplifying x = -0.6666666667

Subproblem 2

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3

Solution

x = {-0.6666666667, 3}

See similar equations:

| 2x(3x^3-4x^2+x-8)=0 | | x^2-13x-114= | | 4x^9+8x^8+12x^7+8x^6= | | (8r+3t)-[2-(t+3r)]=0 | | 3(7x+5)=2(4x+3) | | 2x-20=7x | | 9x+6-7x-5=5 | | x-0.19(x)=18 | | -11+3x=20 | | ln(x-2)ln(x)=0 | | (12)a*a-13a=35 | | 2r^3t^3-4r^4t^2= | | 6x+8y^3+300=0 | | 3x+4x+2x=9 | | 3x-6=-3(x+2) | | h(x)=3x^2+6 | | (4x-5)(-x-7)=0 | | -2(-c-12)=-2-12 | | (24)x*x-14x-3=0 | | (4x+5)(x-7)=0 | | z(x+4)=8 | | V=F(r+B) | | 3(m+1.5)=(2m+3) | | 3(x+8)+9=3x+6 | | 13+7n=4n+4 | | 8n-5-2n=41 | | Y=x^2+-1 | | 2x-11=10x+13 | | (5)x*x+27x+10=0 | | (5)x*x+27+10=0 | | (x+6)(x+7)=(11+x)(4+x) | | 9-6*-.5=14+4*-.5 |

Equations solver categories